DIFFERENCES IN ANTEBRACHI MUSCULAR STRENGTH IN 2021 STUDENTS AND MEDICAL SECURITY WORKERS WIJAYA KUSUMA UNIVERSITY SURABAYA - komaria, desiana komaria; Soekanto, Ayly; Ernawati, Sie (Institute for Research and Community Services (LPPM) of University of Wijaya Kusuma Surabaya, 2024)
Introduction: Muscle strength in the extremities, especially in the upper part, is an organ that is very dominant in daily exercise, namely the hands, arms and also the antebrachial muscles in the upper and lower arms. One of the problems that often occurs is problems with the muscles, such as injuries due to frequent daily activities. Method: The aim is to find out the relationshipDifferences in Antebrachi Musculus Strength in 2021 Class A Students and Security Guard Workers at the Faculty of Medicine, Wijaya Kusuma University, Surabaya. Methodresearch with an observational analysis method where the research uses cross sectional research, namely collecting research sample data which is carried out in one experiment after which the results are collected and data processing continues. Results: The data that has been collected fulfills the criteria requirements, namely 30 samples, after which the data is entered into the SPSS 26 application. Based on the results of this research, the calculated t is 3.616 which is smaller than (0.05). Conclusion: The results of this research indicate that there is a significant relationship between the strength of the antebrachial muscles in 2021 Class A students and security guard workers at the Faculty of Medicine, Wijaya Kusuma University, Surabaya.